Hydroxychloroquine and QTc prolongation in patients with COVID-19: A systematic review and meta-analysis (2020)
Background Among many drugs that hold potential in COVID-19 pandemic, chloroquine (CQ), and its derivative hydroxychloroquine (HCQ) have generated unusual interest. With increasing usage, there has been growing concern about the prolongation of QTc interval and Torsades de Pointes (TdP) with HCQ, especially in combination with azithromycin. Aims This meta-analysis is planned to study the risk of QTc prolongation and Torsades de pointes (TdP) by a well-defined criterion for HCQ, CQ alone, and in combination with Azithromycin in patients with COVID-19. Methods A comprehensive literature search was made in two databases (PubMed, Embase). Three outcomes explored in the included studies were frequency of QTc > 500 ms (ms) or ΔQTc > 60 ms (Outcome 1), frequency of QTc > 500 ms (Outcome 2) and frequency of TdP (Outcome 3). Random effects method with inverse variance approach was used for computation of pooled summary and risk ratio. Results A total of 13 studies comprising of 2138 patients were included in the final analysis. The pooled prevalence of outcome 1, outcome 2 and outcome 3 for HCQ, CQ alone with or without Azithromycin were 10.18% (5.59–17.82%, I2 – 92%), 10.22% (6.01–16.85%, I2 – 79%), and 0.72% (0.34–1.51, I2 – 0%) respectively. The prevalence of outcome 2 in subgroup analysis for HCQ and HCQ + Azithromycin was 7.25% (3.22–15.52, I2 – 59%) and 8.61% (4.52–15.79, I2 – 76%), respectively. The risk ratio (RR) for outcome 1 and outcome 2 between HCQ + Azithromycin and HCQ was 1.22 (0.77–1.93, I2 – 0%) & 1.51 (0.79–2.87, I2 – 13%), respectively and was not significant. Heterogeneity was noted statistically as well clinically (regimen types, patient numbers, study design, and outcome definition). Conclusion The use of HCQ/CQ is associated with a high prevalence of QTc prolongation. However, it is not associated with a high risk of TdP.